Negative bureaucratic behavior and development the case of the bureau of internal revenue - Briones, Leonor M. (1979)
The prevailing administrative culture of the Bureau of Internal Revenue (BIR) tolerates corruption despite legal and administrative sanctions prohibiting negative bureaucratic behavior. Cases are presented to illustrate two kinds of corruption-internal corruption which is done without direct collusion with the client and external corruption in which the bureaucrat colludes and bargains with the client at the boundary exchange level. Reforms have, however, been instituted to minimize, if not eliminate corruption in the BIR. Still,
since corruption has been found to have a negative effect on development, adoption of measures to eliminate corruption must not be separated from the larger goal of forming a more development-oriented society.
Keywords: Government agencies -- Corrupt practices; Corruption -- Government policy; Philippines. Department of Finance. Bureau of Internal Revenue; Philippines. Department of Finance. Bureau of Internal Revenue -- Corrupt practices